The Discourse Construction of the Four-Island Dispute between Aceh and North Sumatra: A Critical Discourse Analysis - Bambang Wibisono; Santuso Santuso; Akhmad Haryono; Akhmad Sofyan (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study aims to examine the discourse construction of the four-island dispute between Aceh and North Sumatra in local media coverage. It employs a critical qualitative descriptive approach using Norman Fairclough’s critical discourse analysis model. The data consist of linguistic elements, including diction, sentence structures, and modality that construct the discourse of the dispute. The data sources are two local media outlets, Aceh Portal and Sumut Pos, with two purposively selected news articles from each, published during May–June 2025, when the issue reached its peak intensity and public attention. Data were collected through close reading and note-taking techniques, while data analysis was conducted through Fairclough’s three dimensions: textual, discursive practice, and sociocultural practice. The findings reveal significant differences in the ideological construction of the dispute between the two media. At the textual level, Aceh Portal tends to frame the dispute as administrative injustice and a struggle to defend historical rights, whereas Sumut Pos represents it as a legitimate and final legal-administrative issue. At the level of discursive practice, these differences are reflected in the selection of perspectives, sources, and patterns of text production. At the sociocultural level, the coverage reflects tensions between state hegemony and regional resistance shaped by historical, political, and economic factors. This study highlights that local media function not merely as channels of information but also as ideological actors in constructing and framing territorial disputes.